Reflections of an illuminator. Issue 2 (1st June 2017) - Read, Mark
Mark Read, initiator of The Illuminator, looks back over the past five years of this renowned art-activist visual culture project. Emerging out of the Occupy Wall Street movement, The Illuminator art collective has staged hundreds of interventions in public spaces, using guerilla video projections to amplify the messages of social justice activist groups all over the country, and internationally.In this essay, Read assesses the strategic value of such semiotic strategies within social movements, and explores important connections between the political goals of the collective, and how it organizes itself economically.